Abses Otak - Andrea Valentino; Gebby Puspita Angraini (Fakultas Kedokteran Universitas Riau, 2019)
Cerebral abscess may rise from hematogenous spread, contiguous spread, or direct trauma. Some risk factors include pulmonary abcess or AV fistulas, congenital cyanotic heart disease, immune compromise, chonic sinusitis / otitis, dental problems. Symptoms are similar to any other mass lessions but tend to progress rapidly. Streptococcus is most common organism that recovered, while up to 25% of cases sterile. Staging of cerebral abcess is very important to differentiate therapeutic management based on clinical findings and imaging. Mortality and morbidity rate has been reduced due to improvement in antibiotics, surgery and ability to diagnose.